Structural and functional characteristics of left ventricular strain in healthy individuals with different physical activity level according to echocardiography - Yu. L. Begrambekova; O. A. Drobyazko; D. V. Skripkina; Ya. A. Orlova; M. N. Alekhin (Кардиоваскулярная терапия и профилактика, 2023)
Aim. To determine the structural and functional characteristics of the myocardium in young people with different levels of physical activity (PA).Material and methods. The study included 108 young people without cardiovascular diseases. Seventy-two people were professional endurance athletes (Group A) and 36 were non-athletes (Group non-A). Anthropometric data were evaluated. Transthoracic echocardiography and assessment of left ventricular (LV) longitudinal, radial and circumferential strain, as well as LV twisting, were performed. PA level in non-A group was determined using International Physical Activity Questionnaire (IPAQ).Results. PA level <600 MET-min/week was revealed in 22,3% of participants, moderate PA (from 600 to 1500 MET-min/week) — in 41,7%, and high (3000 MET-min/week) — in 36% of participants of inactive, moderately active and highly active subgroups, respectively. Group A daily PA level was ~15000 MET-min/week. In non-A group, there were no significant differences in echocardiographic parameters in subgroups with different PA levels. Significant differences with group A were revealed. LV diastolic function was within the normal range in all subgroups. The E/A ratio was higher in subgroups with higher PA (maximum in subgroup A). Significant differences were observed between inactive (p=0,027) and athletes/moderately active (p=0,017) subgroups. Longitudinal, radial and circular strain characteristics did not differ in A and non-A groups and were within normal range.Conclusion. In young people without cardiovascular diseases with PA ranges from extremely low to those recommended by WHO, the structural and functional myocardial characteristics were within age normal range and significantly differed from those of professional athletes. In professional athletes, these parameters also remained within the age normal range. Myocardial strain characteristics were within the normal range in all participants